The effectiveness of oral irrigators on periodontal health status and oral hygiene of orthodontic patients: a systematic review and meta-analysis - Zahra Zarei; Maryam Yazdi; Leila Sadeghalbanaei; Shabnam Tahamtan (BMC Oral Health)
Abstract Background An Oral irrigator, known as a dental waterjet (DWJ), is an adjunctive oral hygiene tool to remove dental plaque. The aim of this study was to systematically evaluate the effectiveness of oral irrigators on orthodontic patients’ oral hygiene and periodontal status. Methods A comprehensive search was undertaken in five electronic databases (PubMed, EMBASE, Web of Science, Scopus, and Cochrane) up to 1 May 2024. Clinical trials comparing DWJ with other adjunctive tools or no adjunctive in healthy orthodontic patients were included. The outcome was periodontal health condition measured by periodontal indexes. The risk of bias of the included studies was assessed using the Cochrane risk of bias tool. Random- effects meta- analyses of mean differences (MD) with their 95% confidence intervals (CI) were conducted and the overall quality of evidence was evaluated by GRADE approach. Results Seven trials were included in the meta-analysis (Two with low, and others with unclear risk of bias). There was no statistically significant difference between automatic toothbrush (ATB) with DWJ and ATB alone in the gingival index (GI) (MD = 0.00; 95% CI -0.17- 0.18) (low quality of evidence). No statistically significant differences were found between (ATB + DWJ) and manual toothbrush (MTB) alone in the GI (MD= -0.11; 95% CI -0.31- 0.09) (very low quality of evidence). Also, no significant difference was detected between the two groups in the Plaque index (PI) (MD= -0.12; 95% CI -0.36- 0.11) (very low quality of evidence). There was no statistically significant difference between (MTB + DWJ) and MTB alone in the GI (MD= -0.06; 95% CI -0.16- 0.03) (very low quality of evidence). No statistically significant differences were revealed between the two groups in the PI (MD= -0.33; 95% CI -0.97- 0.32) (very low quality of evidence). No statistically significant improvements were found between these two groups in bleeding index (BI) (MD= -0.05; 95% CI − 0.12 − 0.01) (low quality of evidence). Conclusions Adding DWJ to either manual or automatic toothbrushes did not significantly enhance oral health of orthodontic patients. Orthodontists could recommend their patients to use either of these toothbrushes with or without DWJ. Further clinical trials are needed. Trial registration number The protocol of this study was registered on PROSPERO with the ID # CRD42023465849.